Implementasi Perencanaan Media Pembelajaran Pada Pembelajaran Pendidikan Agama IslamDi SMA Negeri 2 Jakarta - Iqbal Abdul Kholiq; Maria Ulfa (Journal Education Innovation (JEI), 2024)
Learning media planning requires a deep understanding of the learning objectives to be achieved. The aim of this research is to look at and analyze the application of learning media planning to the learning of Islamic Religious Education (PAI) in State High School 2 Jakarta. The researchers used a qualitative approach to the type of case study. Data collection techniques included observations in the classroom, interviews with PAI teachers, and analysis of documentation on the use of learning media. Research results showed that learning media planning at Jakarta State High School 2 was successful in increasing student participation during learning. Taking advantage of a variety of learning methods, such as multimedia presentations, video learning, and interactive digital resources, makes the class dynamic and exciting. Students are more involved in discussions, media-based projects, and other learning activities. The use of learning media helps diversify learning approaches. To adapt to the different learning styles of students at Jakarta State High School 2, PAI teachers use kinesthetic, visual, and auditorium media. This method provides variation in the delivery of PAI material and supports students' deeper understanding of religious concepts. One of the positive results of the application of learning media planning is the improved understanding of the PAI materials by students. Hearing methods, such as discussions and presentations, and visual media help visualize the concepts of religion. Kinesthetic activities, like role-playing or simulation, add practical dimensions and hands-on experiences, enhancing a comprehensive understanding of the concept of religion.